If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(y + -5y) + 9 = -6(2y + -1y) + 3 + 3y Combine like terms: y + -5y = -4y -2(-4y) + 9 = -6(2y + -1y) + 3 + 3y Remove parenthesis around (-4y) -2 * -4y + 9 = -6(2y + -1y) + 3 + 3y Multiply -2 * -4 8y + 9 = -6(2y + -1y) + 3 + 3y Reorder the terms: 9 + 8y = -6(2y + -1y) + 3 + 3y Combine like terms: 2y + -1y = 1y 9 + 8y = -6(1y) + 3 + 3y Remove parenthesis around (1y) 9 + 8y = -6 * 1y + 3 + 3y Multiply -6 * 1 9 + 8y = -6y + 3 + 3y Reorder the terms: 9 + 8y = 3 + -6y + 3y Combine like terms: -6y + 3y = -3y 9 + 8y = 3 + -3y Solving 9 + 8y = 3 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 9 + 8y + 3y = 3 + -3y + 3y Combine like terms: 8y + 3y = 11y 9 + 11y = 3 + -3y + 3y Combine like terms: -3y + 3y = 0 9 + 11y = 3 + 0 9 + 11y = 3 Add '-9' to each side of the equation. 9 + -9 + 11y = 3 + -9 Combine like terms: 9 + -9 = 0 0 + 11y = 3 + -9 11y = 3 + -9 Combine like terms: 3 + -9 = -6 11y = -6 Divide each side by '11'. y = -0.5454545455 Simplifying y = -0.5454545455
| 5(5+n)=55 | | x/3-4-10 | | 100+4x=-50 | | (4x^3-39x+35)/(x^2+2x-24) | | 2-7x=-2x+47 | | 0=8*(n+8) | | (1/2)b-2=1 | | 125+13x=21x-75-21 | | 6g^2-43g-40=0 | | 8*(n+10)=112 | | 2-cos^2x=0 | | (x^2+x-12)=0 | | 2-sec^2x=0 | | 54-18+4x=36-2x+15 | | .8x+.2x=(x+400).5 | | (x^2-4)(x^2+x-12)=0 | | (n+4/8)=1 | | 2=x-2-3x+6 | | -5x-5x=35-5 | | Bx-d=ax+c | | 15f^2+37f-8=0 | | m+4m+9m+2= | | 880/74 | | -23+10=m-5 | | 14/63 | | 435/15 | | 5y-10=25x | | C=1000+0.6(Y-200) | | 4x+9=57-4x | | 6x=6(70-x) | | 7t+44=12y+11 | | m+3m-9m= |